The Language of Deviant Teaching in Malaysia - Nordin, Munif Zarirruddin Fikri (JOURNAL OF ADVANCES IN LINGUISTICS, 2018)
As religion covers some abstract and metaphysical concepts, its meanings are subjected to the differences, and somehow interpreted defiantly. This article discusses the language of deviant teaching by referring to the Malay language as a religious language in Malaysia, having the objectives of (1) identifying the pragmatics in the language of deviant teaching, and (2) describing the interpretation of truth in the language of deviant teaching. The discussion is based on the pragmatic concept suggested by Crystal [1]) that language users have choices when using language, and Russell’s approach [2] to meaning and interpretation in the philosophy of language. The data used in the discussion relate to the use of Malay Islamic words by two Muslim groups in Malaysia which are identified as deviant teachings, namely Tareqat Amirul Mukminin in the state of Perak and Tarikat al-Tijani in the state of Kelantan. The results show that there is a central cause of pragmatics in the language of deviant teaching which is the formulation of the identity. The results also show that the interpretation of truth in the language of deviant teaching is relatively associated with the cult of the leaders by referring them as being beyond superior and very outstanding.